Nursing Activities and Role Variation in Veterans Health Administration Primary Care - Chelsea McConnell; Elvira E. Jimenez; Charlene Pope; Rong Guo; Traci Solt; Laura Coyle; Jami Falk; Evelyn T. Chang (JAMA Network Open, 2026)
This quality improvement study surveyed Veterans Health Administration (VHA) nurses to better understand primary care nursing activities and their alignment with nurses’ training and scope of work.